2019
DOI: 10.1515/jcim-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Aflatoxin B1-induced gastrointestinal injuries by Eucalyptus oil in rats

Abstract: AbstractBackgroundEucalyptus oil (EO), derived from Eucalyptus species, possesses vast remedial and healing properties, although its gut health-promoting properties have not been well investigated. In this study, we investigated the chemical composition of a commercial EO formulation and its potential role in protecting against aflatoxin B1 (AfB1)-induced gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…testes and hypothalamus of rats treated with AFB1, indicating proinflammatory activity of AFB1 in the reproductive tissues of male rats. AFB1-induced elevation of NO and MPO levels was reported by Akinrinde et al(Akinrinde et al, 2019).Adedara et al observed a similar result (Adedara et al, 2019). Consequent treatment with 3-IPA (25 and 50 mg/kg) restored the levels of these pro-inflammatory mediators to similar levels with the control rats, demonstrating the anti-inflammatory role of 3-IPA in the testis's epididymis and hypothalamus of rats, compared with AFB1 alone.XO can generate reactive oxygen species (ROS)-including hydrogen peroxide (H 2 O 2 ) and superoxide anion (O 2•− )-contribute F I G U R E 11 A proposed mechanism for 3-IPA on AFB1-induced oxidative stress, inflammation and apoptosis in the neuronal and reproductive organs of male Wistar rats.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…testes and hypothalamus of rats treated with AFB1, indicating proinflammatory activity of AFB1 in the reproductive tissues of male rats. AFB1-induced elevation of NO and MPO levels was reported by Akinrinde et al(Akinrinde et al, 2019).Adedara et al observed a similar result (Adedara et al, 2019). Consequent treatment with 3-IPA (25 and 50 mg/kg) restored the levels of these pro-inflammatory mediators to similar levels with the control rats, demonstrating the anti-inflammatory role of 3-IPA in the testis's epididymis and hypothalamus of rats, compared with AFB1 alone.XO can generate reactive oxygen species (ROS)-including hydrogen peroxide (H 2 O 2 ) and superoxide anion (O 2•− )-contribute F I G U R E 11 A proposed mechanism for 3-IPA on AFB1-induced oxidative stress, inflammation and apoptosis in the neuronal and reproductive organs of male Wistar rats.…”
supporting
confidence: 68%
“…NO, MPO and TNF‐α were prominently increased in the epididymis, testes and hypothalamus of rats treated with AFB1, indicating pro‐inflammatory activity of AFB1 in the reproductive tissues of male rats. AFB1‐induced elevation of NO and MPO levels was reported by Akinrinde et al (Akinrinde et al., 2019). Adedara et al observed a similar result (Adedara et al., 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Outstandingly, in the present study, the pre-treatment of rats with 100 mg/kg of EO conferred marked protection from gamma-rays induced gastric ulceration as evidenced by the intact mucosal layer, absence of haemorrhage and necrosis. The EO at the doses (50 and 100 mg/kg) for 14 days protected against Aflatoxin B1-induced injuries in stomach and intestinal tissues that could be used in the management of gastrointestinal syndromes in rats (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The genus Eucalyptus L'Heritier comprises about 300 species contains volatile essential oil in their leaves (6) . Eucalyptus oil (EO) has amazing widespread biological activities including antimicrobial, antiseptic, antioxidant, chemotherapeutic (7,8) , respiratory and gastrointestinal effects (9,10) as well as wound healing (11) . No research article has yet assessed the radioprotective role of EO against gamma-rays induced gastric ulceration in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary toxicity of AFB 1 has been observed in vivo on male albino rats [117]. Gastrointestinal toxicity of AFB 1 has been described in vivo on rats [118], pigs [119], and chickens [120]. The genotoxic effect has been observed in vivo on mice [110].…”
Section: Recent Data On Aflatoxin Toxicitymentioning
confidence: 99%